THE MAIN CHARACTERISTICS OF MUSIC IN THE TELEVISION COMMERCIALS OF POPULAR BRANDS - Szabo, Daniel (PEOPLE: International Journal of Social Sciences, 2017)
Television advertisement is one of today’s most popular tools and forms of audiovisual marketing communication. It can reach a huge number and a wide range of viewers. Typically, most of them include some sort of music which can contribute to the atmosphere of the advertisement, and thereby support its message. Examining the connections and relationships from the perspective of music theory in them, we can say that the individual components of music can influence the mood of the music. In this paper, in an exploratory nature, the music of advertisements of the companies with the highest brand values was analyzed. For this study, television commercials served as a basis. They are made up of a number of components. The aim was to find solutions and correlations that can help marketing communication in a conscious use of music in the commercials, from the perspective of planning and implementation and utilization. In the light of the results of the tests, between the main characteristics of music used in commercials of the world’s most valuable brands, statistically detectable relationships can be detected. Accordingly, by partly accepting the hypothesis of the study, it can be concluded that the formation of the main musical theoretical characteristics of the analyzed advertising genres correlates with each other.